Ownership concentration and sensitivity of executive pay to accounting performance measures: Evidence from publicly and privately-held insurance companies - Ke, Bin; Petroni, Kathy; Safieddine, Assem (Journal of Accounting and Economics, 1999)
We investigate the relation between CEO compensation and accounting performance measures as a function of ownership structure. We use publicly-held property-liability insurers to consider the relation for firms with diffusely-held ownership and use privately-held property-liability insurers to consider the relation for firms with closely-held ownership. We find a significant positive association between return on assets and the level of compensation for publicly-held insurers. Consistent with optimal contracting theory, we find no such relationship for privately-held insurers. Results suggest that within closely-held firms CEO compensation is less based on objective measures like accounting information and more on subjective measures.